The importance of the syllables (EN) (KUR) (A) (É) to the Sumerians - Al-Saadi, Hussain A. (Al-Adab Journal, 2021)
This research deals with an important form of Sumerian syllables, each of which has different meanings, The meaning of (EN) indicates the throne and the master, The phrase "KUR" refers to the mountain and the lower world, While the phrase (A) refers to the secret of life, which is water in all its forms and forms, And the phrase (É) expresses the institution represented by the temple and the place of residence of the people of the rulers who settled in palaces and the common people who lived in humble homes, And the reason for choosing these syllables to be the subject of our research (the importance of the syllables (EN) (KUR) (A) (É) among the Sumerians, It was because of their frequent circulation in the early Sumerian texts discovered, so we tried to shed light on the reasons for the interest in these phrases by the Sumerian population, and even for those who came after them from the Akkadians who did not deny the importance of these phrases, But they took it from the Sumerians and created for it linguistic syllables that express the same Sumerian meaning in a way that fits with their insular character in their dealings with various aspects of life, The vocabulary of the Sumerian syllables remained looming over the island’s linguistic atmosphere that the Akkadians brought from the Babylonians and the Assyrians, Often we find that bilingual linguistic texts include both Sumerian and Akkadian syllables in the same text, This of course is one of the characteristics of the Sumerian and Akkadian Rafidian languages.